Kegiatan Pengabdian Masyarakat pada RT 36 Kelurahan Gunung Samarinda Baru Melalui Kegiatan Renovasi Fasilitas dan Sosialisasi Pembelajaran - Yansyah, Deli; Rahmah, Khairunnisa; Haical Syafihi, Syuck; Ilham, Taufik; Adinda Thalia Salsabila, Nurul; Adita Nur Syafitra, Mohammad; Deani Amanda, Nasya; Andrian, Naufal; Atha Arrafi, Muhammad; Azinda Amrizon, Nur; Aryani, Defi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The Student Service Program (PMMD) Group D2 in RT 36, Gunung Samarinda Baru Subdistrict, Balikpapan City, aimed to improve community welfare through educational and environmental approaches. The program included educational sessions for children at the Al-Qur’an Education Center (TPA) focusing on basic mathematics and English, the construction of segregated waste bins to support waste management, and the renovation of the neighborhood security post (poskamling) to serve as a cleaner and more functional community facility. The implementation methods involved field observations, interviews with residents and the local RT head, and participatory approaches in carrying out the initiatives. The results showed improved understanding among children, increased community awareness of environmental hygiene, and the revitalization of the security post’s function. This program demonstrates a tangible contribution to community empowerment and serves as a model for locally driven community engagement.